Taurolidine Lock in Home Parenteral Nutrition in Adults: Results From an Open-Label Randomized Controlled Clinical Trial. (March 2015) - Klek, Stanislaw; Szczepanek, Kinga; Hermanowicz, Adam; Galas, Aleksander
Background and Aim : Many techniques have been tested to reduce the incidence of catheter-relater bloodstream infections (CRBSIs) during home parenteral nutrition (HPN). One of these methods, taurolidine lock, has shown some potential in several studies, but it has been studied primarily in patients with a relatively high CRBSI rate. Therefore, the aim of this study was to analyze the clinical value of taurolidine in patients receiving HPN who have a low infection rate. Methods : The CRBSI ratio at the Skawina HPN center has remained at 0.3–0.4 episodes/patient/y for the past 7 years. In November 2012, 30 patients (17 men, 13 women, mean age 52.3 years) were randomized to 1 of 3 groups: 2% taurolidine lock (group A), 1.35% taurolidine + citrate lock (B), and control—saline flush (C). Patients were observed for 12 consecutive months for catheter-related complications. Blood cultures were collected in each case in which an infection was suspected. Results : The total number of catheter days reached 10, 968, with the following number of days per group: group A, 3658; group B, 3650; and group C, 3660. No complications were observed in the control group, while patients in the study groups had 1 catheter infection (group A) and 1 occlusion (group B). The CRBSIs were treated successfully with antibiotics. The cost of treatment in groups A and B was significantly higher than that in group C ( P < .05). Conclusion : The study did not observe any additional clinical value of taurolidine in patients receiving HPN who have a low infection rate and found low cost-effectiveness. Taurolidine should most likely be used only in patients with a high CRBSI rate.